HKS Misinfo Review 2021
DOI: 10.37016/mr-2020-79
|View full text |Cite
|
Sign up to set email alerts
|

Review of social science research on the impact of countermeasures against influence operations

Abstract: Despite ongoing discussion of the need for increased regulation and oversight of social media, as well as debate over the extent to which the platforms themselves should be responsible for containing misinformation, there is little consensus on which interventions work to address the problem of influence operations and disinformation campaigns. To provide policymakers and scholars a baseline on academic evidence about the efficacy of countermeasures, the Empirical Studies of Conflict Project conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…25 Looking at outcomes such as beliefs, intended behaviour, knowledge, and observed behaviour, the studies indicate that fact checking can reduce the influence of exposure to false information on people's beliefs as well as their propensity to share misinformation and disinformation. 25 In terms of fact checking interventions, most of the included studies evaluated the effects of disinformation disclosure, which is when the platform informs a user that they have come in contact, shared, or interacted with disinformation; many others studied content labelling using a fact checking tag, funding tag or outdated tag, and some examined interventions that educate users to identify disinformation. 25 Although most of these countermeasures are proved effective, they don't represent the major interventions used by social media platforms in the real world, such as content moderation (removal or suspension of account or content).…”
Section: Infodemics-a Key Part Of Pandemic Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…25 Looking at outcomes such as beliefs, intended behaviour, knowledge, and observed behaviour, the studies indicate that fact checking can reduce the influence of exposure to false information on people's beliefs as well as their propensity to share misinformation and disinformation. 25 In terms of fact checking interventions, most of the included studies evaluated the effects of disinformation disclosure, which is when the platform informs a user that they have come in contact, shared, or interacted with disinformation; many others studied content labelling using a fact checking tag, funding tag or outdated tag, and some examined interventions that educate users to identify disinformation. 25 Although most of these countermeasures are proved effective, they don't represent the major interventions used by social media platforms in the real world, such as content moderation (removal or suspension of account or content).…”
Section: Infodemics-a Key Part Of Pandemic Managementmentioning
confidence: 99%
“…25 In terms of fact checking interventions, most of the included studies evaluated the effects of disinformation disclosure, which is when the platform informs a user that they have come in contact, shared, or interacted with disinformation; many others studied content labelling using a fact checking tag, funding tag or outdated tag, and some examined interventions that educate users to identify disinformation. 25 Although most of these countermeasures are proved effective, they don't represent the major interventions used by social media platforms in the real world, such as content moderation (removal or suspension of account or content). 25 Using randomised experiments based on a hypothetical scenario that includes information that is later refuted, two studies in cognitive psychology identified a "continued influence effect" of misinformation.…”
Section: Infodemics-a Key Part Of Pandemic Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Various works capture the diverse technical countermeasures both proposed and undertaken by research and social media platforms (Courchesne et al, 2021;Yadav, 2021;Gausen et al, 2021). Roughly, it is differentiated between deletion, redirection or reduction of visibility of posts, and behavioral approaches tackling users' perception of social media content by warnings or labeling.…”
Section: Suitability Of Existing Approachesmentioning
confidence: 99%